2001
DOI: 10.1177/104063870101300307
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Determination of Ergot Alkaloids in Seed, Straw, and Digesta Samples Using a Competitive Enzyme-Linked Immunosorbent Assay

Abstract: Abstract. Ergot alkaloids present in endophyte-infected (Eϩ) tall fescue cause fescue toxicosis and other toxic effects in livestock that consume infected plant tissue, leading to significant financial losses in livestock production each year. The predominant method currently in use for quantifying ergot alkaloid content in plant tissue is through high-performance liquid chromatography (HPLC), which quantifies the amount of ergovaline, one of many ergot alkaloids in Eϩ plant tissue. The enzyme-linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…In addition to the instrumental approaches described here, an immunological approach has been successful for detecting and quantifying ergot alkaloids in aggregate (e.g., Hiatt, Hill, Bouton, & Stuedemann, 1998;Hill, Thompson, Dawe, & Stuedemann, 1994;Schnitzius, Hill, Thompson, & Craig, 2001). In this case, the antibody was raised against lysergol coupled to human serum albumin and cross reacts with ergovaline and a variety of other ergot alkaloids.…”
Section: Alternative Methodsmentioning
confidence: 99%
“…In addition to the instrumental approaches described here, an immunological approach has been successful for detecting and quantifying ergot alkaloids in aggregate (e.g., Hiatt, Hill, Bouton, & Stuedemann, 1998;Hill, Thompson, Dawe, & Stuedemann, 1994;Schnitzius, Hill, Thompson, & Craig, 2001). In this case, the antibody was raised against lysergol coupled to human serum albumin and cross reacts with ergovaline and a variety of other ergot alkaloids.…”
Section: Alternative Methodsmentioning
confidence: 99%
“…This method has been successfully used to measure total ergot alkaloid concentrations in plant and fungal tissues Kelley, 1990, 1992;Hill and Agee, 1994;Schnitzius et al, 2001), digesta (Hill and Agee, 1994), urinary and biliary excretions (Stuedemann et al, 1998;Hill et al, 2000), and animal fat (Realini et al, 2005). However, the method suffers from a lack of selectivity in that it does not distinguish one ergot alkaloid from another.…”
Section: Analytical Optionsmentioning
confidence: 98%
“…The ELISA method Kelley, 1990, 1992;Hill and Agee, 1994;Schnitzius et al, 2001) excels in sensitive and rapid analysis for total ergot alkaloids. This method has been successfully used to measure total ergot alkaloid concentrations in plant and fungal tissues Kelley, 1990, 1992;Hill and Agee, 1994;Schnitzius et al, 2001), digesta (Hill and Agee, 1994), urinary and biliary excretions (Stuedemann et al, 1998;Hill et al, 2000), and animal fat (Realini et al, 2005).…”
Section: Analytical Optionsmentioning
confidence: 99%
“…However, the ELISA assay lacks selectivity as it does not differentiate between ergot alkaloids which have necessitated the use of chromatographic methods to detect specific ergot alkaloids (Schultz et al, 2006; De Lorme et al, 2007; Foote et al, 2012; Wang et al, 2013). Schnitzius et al (2001), compared HPLC and ELISA detection of ergot alkaloids and found the methods were inconsistent in their identification of alkaloids, concluding that both had their advantages and disadvantages. Antigen (ergot alkaloids) detection is restricted to the specificity of the antibody used in the ELISA test.…”
Section: Discussionmentioning
confidence: 99%